The Qur’an’s Point of View on Women as Shepherds in Teaching Islamic Rulings in Society | وجهة نظر القرآن حول المرأة باعتبارها راعية في تعليم الأحكام الشرعية في المجتمع - Hamka Hasan; Atrasina Mazaya (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
The research aims to know the role of women in teaching legal rulings before society in Surat An-Nahl: 125, a comparative study between the interpretations of Al-Bahr Al-Moheet and Nizam Al-Durar in the proportion of verses and surahs. As for the research method, it is the comparative method, which is that the interpreter relies on a group of Qur’anic verses in one place, so he explores the views of the interpreters following what was written in the interpretation of that sentence of verses by describing the methods of interpretation of Sheikh Abi Hayyan Al-Andalusi and Sheikh Burhan Al-Din Al-Baq’i through their interpretations, and then I analyze their ideas about the role of women in teaching Islamic rulings before society in Islam in Surat An-Nahl, verse 125, and then compare their opinion with the discussion. As for the method of this research, it is a library method by collecting information from sources and references related to the topic from books of interpretation. and the sciences of the Qur’an. One of the results of this research is that the Sufi color that approached the interpretation of Abu Hayyan Al-Andalusi and learned the occasion when interpreting the Bekaa’i, this interpretation was able to draw the role of women in teaching the legal rulings before the community. Abu Hayyan al-Andalusi and al-Biqaa’i said that God commands the caller to call to the religion of Islam with wisdom, i.e. the Qur’an, and by the preaching of the Qur’an, he means by good exhortation and by means of arguing with kindness and gentleness. This is the way to achieve success in the field of calling to the path of God.